2007
DOI: 10.1007/s00380-006-0961-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Doppler imaging adds incremental value in predicting exercise capacity in patients with congestive heart failure

Abstract: Left ventricular (LV) systolic and diastolic parameters derived from Doppler echocardiography have been used widely to predict functional capacity but diastolic filling is affected by various factors. Tissue Doppler imaging (TDI) that records systolic and diastolic velocities within the myocardium and at the corners of the mitral annulus, has been shown to provide additional information about regional and global LV function. The goal of this study was to examine whether TDI-derived parameters add incremental v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 27 publications
2
35
0
1
Order By: Relevance
“…In another study, E/E 0 was the most powerful predictor not only of exercise capacity but also of reduced peak oxygen uptake. An E/E 0 -ratio [ 7.5 was able to predict a reduction of peak oxygen uptake B 14 ml/min per kg with high sensitivity and specificity [66]. Since diastolic dysfunction and elevated filling pressures are associated with elevated levels of natriuretic peptides, the level of BNP in relation to exercise capacity was investigated in patients with exertional dyspnea and isolated diastolic dysfunction.…”
Section: Diastolic Dysfunction and Exercise Capacitymentioning
confidence: 99%
“…In another study, E/E 0 was the most powerful predictor not only of exercise capacity but also of reduced peak oxygen uptake. An E/E 0 -ratio [ 7.5 was able to predict a reduction of peak oxygen uptake B 14 ml/min per kg with high sensitivity and specificity [66]. Since diastolic dysfunction and elevated filling pressures are associated with elevated levels of natriuretic peptides, the level of BNP in relation to exercise capacity was investigated in patients with exertional dyspnea and isolated diastolic dysfunction.…”
Section: Diastolic Dysfunction and Exercise Capacitymentioning
confidence: 99%
“…Furthermore, we compared and showed the statistical advantage of VVC as a predictor of exercise capacity versus arterial distensibility and LV diastolic parameters, both established predictors of exercise capacity [6,27]. Though we found significant correlation between aortic distensibility and MVO 2 , it remained only a trend when MVO 2 was corrected for heart rate (peak O 2 pulse).…”
Section: Discussionmentioning
confidence: 80%
“…Admittedly our study is not equipped to elucidate the mechanistic interdependence of diastolic LV filling and Ees or VVC. Other authors have reported that the functional capacity of congestive heart failure patients is influenced by left and right ventricular and left atrial dimensions [29], and more so by LV filling conditions [27].…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the presence of carotid plaques is an independent predictor for the presence of CAD. Meta-analysis by Terzi et al [17] showed a significantly higher diagnostic accuracy when PS predicted future myocardial infarction compared to IMT. However, the metaanalysis of Inabaa et al [18] showed that although the diagnostic accuracy of PS was high,it was not significant compared to C-IMT for CAD detection.…”
Section: Discussionmentioning
confidence: 99%